PENGUJIAN PALABILITAS BEBERAPA HIJAUAN TERHADAP DOMBA DEWASA (OVIS ARIES) - Arrahman, Wildan Dwi; Meriksa Sembiring (Journal of Innovation Research and Knowledge, 2024)
This research aims to determine the effect of several forages on the palability of sheep consumption, body weight gain (g/day) and the percentage of forage requirements based on animal body weight. This research used a non-factorial Completely Randomized Design (CRD) with 6 treatments of forage types and 4 replications. The types of forage treatments tested were: P1 = Elephant Grass (Pennisetum purpureum), P2 = Pakchong Grass (Pennisetum purpureum cv Thailan), P3 = Elephant Grass (Pennisetum purpureum), P4 = Lamtoro Leaves (Leucaena leucocephala, P5 = Jackfruit Leaves (Arthocarpus heteropillus)), P6 = Gamal Leaves (Gliricidia sepium), so 24 plots are needed and in each plot there are 2 individuals (1 male and 1 female). Palability testing of forage uses adult sheep aged 1.0 - 1.5 years with a body weight of less than 20 kg. The feeding technique is carried out at 09.00 every morning by giving each forage 4.0 kg/plot (2.0 kg/head). After one hour, the forage given is pulled and weighed to calculate the weight of forage consumed in one hour (weight of forage given – weight of forage remaining in one hour), in addition to the palatability of grass forage compared to woody forage. The parameters observed were the level of palatability of sheep towards forage (feed consumption in the first 1 hour) and comparing the consumption of grass type forage with woody type of forage. The palatability measurements for each treatment were carried out 6 times. The data obtained were averaged and analyzed statistically and if significantly different, continued with testing with DMRT. The results of research analysis testing the palability of forage for livestock by sheep were found to be significantly different (p < 0.05) with the greatest palability being Pakchong grass (H2) and Lamtoro (H5) and the lowest palability being the use of gamal leaf forage (H6). Animal feed with high palability using grass forage compared to woody forage (palability of grass forage > palability of woody forage).